Controle de qualidade e atividade biológica de Sida rhombifolia L. - Machado, Luísa Mulazzani (2012)
Sida rhombifolia L belongs to the family Malvaceae, it is native to the American continent and can be found in all regions of Brazil. It is popularly known as prickly sida , and used in traditional medicine as anti-inflammatory, antidiabetic and lipid lowering. The aim of this study was to determine and evaluate the physical and chemical parameters of quality in the four seasons and the aerial parts and roots of the plant drug; determining the content of total polyphenols, flavonoids and tannins in the extracts of the aerial parts and roots of S. rhombifolia in four seasons; evaluating the antimicrobial and antioxidant activity in these same extracts; investigating the hypoglycemic and lipid lowering activity of extracts that have a higher content of flavonoids, as well as to analyze biochemical parameters of liver, kidney and pancreatic toxicity and cytotoxicity in cells NCTC clone 929 by incorporation of neutral red dye. The drug was collected at the four seasons in Santa Maria, RS, separated into aerial parts and roots and made hydroethanolic extracts 70% from each of these collections. The physico-chemical parameters varied according to the plant part analyzed and the season. The values found for strange matter, determination of water and ash insoluble in hydrochloric acid are consistent with those established for herbs. The winter collection showed higher content of total ash, both to shoots (21.20%) and roots (17.63%). The swelling rates varied significantly among the aerial parts and roots, and the highest rates obtained for each of the samples were collected in summer (35.47%) and autumn (18.40%), respectively. There were significant differences between the content of total polyphenols and flavonoids throughout the year and these have focused differently from the aerial parts and roots. The content of tannins and did not suffer seasonal variation nor the distribution between the parties analyzed the plant. The extracts of the aerial parts (172.50 g / mL) and roots (374.08 g / mL) of winter presented the best antioxidant activity. Extracts of S. rhombifolia showed good antibacterial activity while showed no activity against fungi. The extracts of the aerial parts and roots of the summer of the winter showed no hypoglycemic and lipid lowering activity in healthy animals, the markers of liver, kidney and pancreatic damage did not vary in relation to the control group, and the IC50 obtained at the cytotoxicity assays were 8.88 mg/mL e 12.57 mg/mL, respectively.